Beauty Influencer Review and Their Impact on Shopee Consumer Purchase Decisions - Utami, Nidya Nida (International Journal Administration, Business & Organization, 2022)
One marketing strategy is to use influencer marketing services, as well as beauty products, be it skincare, make up or body care. Reviews given by Beauty influencers are considered to have an impact on meeting the information needs about a product; the way it is conveyed is usually persuasive. The purpose of this research is to determine the effect of beauty influencer reviews on buyer decisions and to find out how much influence this has in the Department of Business Administration, Bandung State Polytechnic. This study uses a descriptive survey method, namely, the assessment is carried out by distributing questionnaires via GForm to respondents. Data processing was carried out using the normality test method, linearity test, and simple linear regression analysis.